2006
DOI: 10.1089/aid.2006.22.695
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and Unique Recombinant Forms of HIV Type 1 Containing Subsubtype A2

Abstract: HIV-1 strains containing subsubtype A2 are relatively rare in the pandemic but have been repeatedly identified in Kenya, where candidate vaccines based in part on subtype A, but not A2 strains, may be evaluated. Among the most recent is CRF16_A2D, a circulating recombinant form (CRF) whose prototypes are complete or partial HIV-1 sequences from Kenya, Korea, and Argentina. Using samples from blood bank discards in Kenya and complete genome sequencing, this report further documents CRF16_A2D and related recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…However, only two Kenyan full-length clade C and three Kenyan fulllength clade D sequences have been published, making the source of the clade C and D in these recombinants unknown. 12,[31][32][33] Phylogenetic analysis of the nonrecombinant clade A1 sequences from this cohort revealed significant viral diversity. This was observed despite the cohort members all practicing sex work in the same small community of Pumwani, Kenya, which suggests that HIV-1 transmission events likely occurred in close physical proximity.…”
Section: Discussionmentioning
confidence: 88%
“…However, only two Kenyan full-length clade C and three Kenyan fulllength clade D sequences have been published, making the source of the clade C and D in these recombinants unknown. 12,[31][32][33] Phylogenetic analysis of the nonrecombinant clade A1 sequences from this cohort revealed significant viral diversity. This was observed despite the cohort members all practicing sex work in the same small community of Pumwani, Kenya, which suggests that HIV-1 transmission events likely occurred in close physical proximity.…”
Section: Discussionmentioning
confidence: 88%
“…Subsubtype A2 was first identified from sequences originating in the Democratic Republic of Congo and Cyprus (Gao et al, 2001), and is now also found in Kenya (Visawapoka et al, 2006). In addition, there have been 2 recognised CRF forms, CRF16_A2D and CRF21_A2D, both of which were also identified in Kenya (Visawapoka et al, 2006). CRF16_A2D has also achieved a global spread and has been identified in Korea and Argentina (Gomez-Carrillo et al, 2004).…”
Section: The Global Distribution Of Hiv-1 Subtypes and Crfsmentioning
confidence: 98%
“…In addition, CRF01_AE is one of the major strains found in Thailand and Southeast Asia (McCutchan et al, 1992;Tovanabutra et al, 2004). Subsubtype A2 was first identified from sequences originating in the Democratic Republic of Congo and Cyprus (Gao et al, 2001), and is now also found in Kenya (Visawapoka et al, 2006). In addition, there have been 2 recognised CRF forms, CRF16_A2D and CRF21_A2D, both of which were also identified in Kenya (Visawapoka et al, 2006).…”
Section: The Global Distribution Of Hiv-1 Subtypes and Crfsmentioning
confidence: 99%
“…In 1997 CRF16_A2D strain KR004 was first isolated in Korea and later in Kenya and Argentina. 9 In Bangladesh subtype C (41.4%) was the most predominant type followed by CRF07 BC (24.2%) and CRF01 AE (9.1%). [10][11][12] Other types such as subtype A1, B, D and several recombinant forms were also detected.…”
mentioning
confidence: 93%